An experimental investigation on the influence of volume fraction using Straw fiber on the bending and tensile strength of material composites - Arifin, Agus Choirul; Majedi, Farid; Bisono, Rahayu Mekar; Fakhrudi, Yoga Ahdiat; Al. Aziz.R, M. Shafwallah (International Journal of Science, Engineering, and Information Technology, 2023)
Rice straw fiber is considered as agricultural residue that has not been widely used other than as animal feed. In addition, the development of composite material technology that uses natural fibers provides interesting mechanical properties to be developed. This paper aims to investigate the effect of different concentrations of fiber usage on bending and tensile strength. The comparison of concentrations of fiber usage are 35% , 40% , 70% dan 80%. The straw fiber was decreased the moisture content using a microwave and  the treatment with NaOH for removed the hemicellulose and lignin in the fibers. The manufacture of this biocomposite uses a matrix of Urea Formaldehyde with a hand lay up technique. The results of the mechanics test(bending and tensile strengths) show that the strength value obtained on the straw fiber variation, namely the highest average value of the Tensile test is 4.82 MPa at a ratio of 40 : 60, while the lowest is 2.88 MPa at a comparison 35 : 65 and and the highest average value of the bending test is at a ratio of 80:20 (6.64 N/mm2), while the lowest is 40:60 (2.45 N/mm2).